Self−determination as an Underlying Value of Mediation Process in Ethical Codes and Legal Scholarship: Tensions between Disputant Autonomy and Substantive Fairness - Onise Tsulaia (Alternative Dispute Resolution Yearbook, 2017)
The paper analyzes two fundamental principles of mediation process – right to self-determination of the parties and essential justice. The paper is based on ethical codes of foreign countries and scientific researches in this field. As there is no ethical code for mediators in Georgia, it is important to rise up awareness of the society regarding mediation as dispute resolution procedure based on ethical principles. Sharing international experience about standards, basic principles of mediation and their interplay is the guarantee for rising up quality of mediation process and supporting court practice.